Brain image fMRI data classification and graphical representation of visual object - Tasneem, Nazifa Afroza; Tithi, Indrani Datta; Shuchi, Ummay Sadia Khanum (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.